A rare case of triplet pregnancy with three different fates of each conceptus - Paul, Sayanti; Mandal, S; Upadhyaya, M; Pramanik, SR (Nepal Journal of Obstetrics and Gynaecology, 2017)
Rate and number of multifetal gestations have increased dramatically largely due to infertility therapy. A number of pregnancies are multifetal to start with followed by spontaneous reduction of one or more embryos. The final outcomes of such pregnancies vary in relation to zygosity, chorionicity and gestational age. In this case report we present a triplet pregnancy resulting from controlled ovarian hyperstimulation followed by intrauterine-insemination in a primarily infertile patient and how it ended up into a singleton pregnancy with no conscious attempts at selective reduction or selective termination. While fighting with problem of multiple pregnancies which comes along with the widespread infertility treatment nature has its own miraculous way to get rid of such. Little patience and watchful expectancy from the part of obstetrician can achieve a healthy live baby without inadvertent complication.